Persepsi Penerapan SAK EMKM Terhadap Kualitas Laporan Keuangan Dalam Masa Pandemi Covid 19 - Uum Helmina Chaerunisak; Teguh Erawati; Epsilandri Septyarini; Dinda Ayu Nur Anisa (Jurnal Literasi Akuntansi, 2021)
Purpose: SMEs are one of the sectors that have been affected by Covid 19 pandemic. SMEs must adapt during the pandemic so their business can survive. One of them is by recording financial statements. However, in practice many SMEs do not record financial statements in accordance with applicable accounting standard. This study aims to determine the effect of implementing SAK EMKM on financial reporting quality during Covid 19 pandemic in SMEs Jawa Tengah and Yogyakarta.Method: The method using quisionnare, then processed and analyzed by SPSS 20 Version.Finding: The results indicate that implementing SAK EMKM has a possitive effect on financial reporting quality.Novelty: Use of SMEs Financial Reports during the Pandemic in Yogyakarta